New Frontiers in Computer-Assisted Career Guidance Systems (CACGS): Implications From Career Construction Theory - Leung, S. Alvin (Frontiers in Psychology, 2022)
This article examined the use of computer-assisted career guidance systems (CACGS) in career intervention. Major CACGS developed in the past decades have made use of the trait-factor approach in their conceptualization and design. The strengths and limitations of existing CACGS in addressing the career development needs of individuals were discussed. The Career Construction Theory (CCT) is proposed to be an emerging paradigm to guide the development of new generations of CACGS. Advancement in technology has made it possible to combine a test-and-tell approach with a meaning construction paradigm to support career development service. A digital system developed in Hong Kong called Infinity is a case-in-point of an application where users could learn about career planning, engage in self and career construction through using the quantitative and qualitative assessment functions and gamified tools, take adaptive career actions over time, and communicate with their supportive systems. Research findings suggested that users of the system reported higher levels of career adaptability and career decision clarity, lesser decision-making difficulties, stronger intention to pursue university education options, and better understanding of what is career planning than non-users. Research and practice implications were discussed.